PERENCANAAN DAN PENERAPAN PREVENTIVE MAINTENANCE MESIN CNC MILLING FZ 2000 - Billy Oktavian, Billy Oktavian (Politeknik Negeri Cilacap, 2023)
An industrial internship is a practical activity for students with the aim of gaining experience from this activity, which can later be used for professional development and human resource development. One of the industrial internships was carried out at a bus body company from Ungaran, namely CV. Like Bodywork. During the industrial internship the author focused on research regarding the planning and implementation of Preventive Maintenance of ABS vacuum pumps on CNC Milling machines FZ 2000. Problems that occurred during the production process using CNC Milling machines with ABS Vacuum pumps were the problem of broken blades, the radiator not running properly. Well, there's an electrical short circuit, the air hoses are leaking, the vacuum pump is leaking or overheating. Planning a maintenance system needs to be done to reduce the number of machine downtime. CV. Laksana Karoseri uses two types of maintenance systems, General Maintenance and Emergency Maintenance. Meanwhile, preventive maintenance activities carried out on the CNC MILLING FZ 2000 machine include daily maintenance, maintenance every 2 months, maintenance every 6 months and annual maintenance. Meanwhile, preventive maintenance on ABS vacuum engine pumps on CNC Milling Machines is known to be carried out every 6 months including checking and replacing the vacuum engine oil using 2 liters of Corena S4 P shell oil for every use reaching 5000 km/hour, cleaning the air filter, maintaining and cleaning the water filter and checking the spindle lubricating fluid.